2017
DOI: 10.1016/j.childyouth.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Testing three pathways to substance use and delinquency among low-income African American adolescents

Abstract: Objective Mounting literature suggests that parental monitoring, risky peer norms, and future orientation correlate with illicit drug use and delinquency. However, few studies have investigated these constructs simultaneously in a single statistical model with low income African American youth. This study examined parental monitoring, peer norms and future orientation as primary pathways to drug use and delinquent behaviors in a large sample of African American urban adolescents. Methods A path model tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…High future orientation and self-esteem are malleable factors that have been generally shown to have a direct relationship to lower rates of youth substance use and delinquency (Chen et al, 2016; Marotta and Voisin, 2017; Robbins and Bryan, 2004). Future orientation is a multi-component process (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…High future orientation and self-esteem are malleable factors that have been generally shown to have a direct relationship to lower rates of youth substance use and delinquency (Chen et al, 2016; Marotta and Voisin, 2017; Robbins and Bryan, 2004). Future orientation is a multi-component process (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although variable‐oriented methods consistently demonstrate that family, neighborhood, and poverty independently contribute to risk for adverse psychosocial outcomes (Evans & Kim, ; Hartinger‐Saunders et al., ; Marotta & Voisin, ), these contexts are understood to be interactional in nature; comprehending the totality of their effects requires moving beyond variable‐oriented methods. This simultaneous consideration of these contexts advances the literature by providing evidence of the differential effects youth experience.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is some indication that adolescent males are more likely to associate with peers engaged in risky behaviours (Svensson, ). Among a community sample of African American youth, Marotta and Voisin () found that risky peer norms was a stronger predictor than parental monitoring of substances use, with those who associated more with peers who engaged in risky behaviours being more likely to report lifetime drug use. Research suggests that African American adolescent females have a lower likelihood of using alcohol as they age and are less likely to be influenced by alcohol drinking peers compared to their White female counterparts (e.g., Watt & Rogers, ).…”
Section: Discussionmentioning
confidence: 99%